Spiral-like Functions associated with Borel Distribution-Type Mittag-Leffler Function - Shrigan, Mallikarjun G.; Thombare, A. A.; Chate, D. N.; Shaba, Timilehin G. (Sarajevo Journal of Mathematics, 2025)
The purpose of the present paper is to obtain some sufficient conditions for analytic functions, whose coefficients are probabilities of the Borel Distribution-Type Mittag-Leffler Function, to belong to the class of spiral-like univalent functions. Further, we discuss the geometric properties of an integral operator related to the Borel Distribution-type Mittag-Leffler Function. Moreover, we investigated and explored some applications of our main results for the error function.